The development of the psychosocial work environment in Denmark from 1997 to 2005 - Pejtersen, Jan H.; Kristensen, Tage S. (Scandinavian Journal of Work, Environment & Health, 2009)
' ' OBJECTIVE ': 'The aim of the study was to elucidate the development of the psychosocial work environment in Denmark from 1997–2005. ' ' METHODS ': 'The analyses were based on two national questionnaire surveys (N1=1062; N2=3517) of randomly selected employees who completed the Copenhagen Psychosocial Questionnaire. The psychosocial work environment was described by 19 scales and 6 single items. ' ' RESULTS ': 'Quality of leadership and social support from supervisors were the only dimensions that saw improvements. The negative developments were: higher work pace, less influence (job control), less possibilities for development (skill discretion), lower level of meaning of work, more role conflicts, decreased role clarity, reduced sense of community, less social support from colleagues, increased conflicts at work, more threats of violence and more slander and gossip. ' ' CONCLUSIONS ': 'The psychosocial work environment in Denmark has deteriorated during the period 1997–2005. This deterioration was seen not just among certain groups of employees but in all subgroups, incorporating gender, age and socioeconomic status. The negative development of a country’s psychosocial work environment is worrying; as such, there is a strong need to change this negative trend.
Keywords: Denmark; psychosocial dimension; psychosocial work environment; questionnaire survey; review; secular trend; stress; systematic review; time trend; work environment